Genotypic evolution and antigenic drift of H9N2 influenza viruses in China from 1994 to 2008 - Sun, Yipeng; Pu, Juan; Jiang, Zhanlei; Guan, Tao; Xia, Yingju; Xu, Qi; Liu, Linqing; Ma, Bo; Tian, Fulin; Brown, E.G.; Liu, Jinhua (Veterinary microbiology, 2010)
H9N2 influenza viruses have been circulating in China since 1994, but a systematic investigation of H9N2 in northern China has not been undertaken since 2004. Here, using the sequences of 22 viruses we isolated from poultry and pigs in northern China during 2003–2008, in combination with sequences available in a public database, we analyzed the evolution of H9N2 influenza viruses in China from 1994 to 2008. Our findings demonstrated that the H9N2 viruses in China underwent extensive reassortment, and novel genotypes continued to emerge. Among 330 viruses, 54 genotypes were observed including 19 novel genotypes that have not been recognized before, and major genotypes were further divided into five series (BJ/94-, G1-, BG-, F/98- and Aq-series). Different epidemiological and biological features among these series were recognized. The BJ/94- and F/98-series viruses were circulating in both southern and northern China, while the other three series viruses were mainly detected in southern China. BJ/94-series influenza viruses predominated in China before 2000 and were gradually replaced by F/98-series viruses that became the predominant viruses since 2004. At least five antigenic groups could be identified over the study period, during which a significant antigenic drift likely occurred between 2002 and 2003. Animal experiments demonstrated that F/98-series viruses were able to replicate and transmit more effectively in chickens than BJ/94-series viruses. The continuing evolution of H9N2 influenza viruses in China emphasizes the importance of H9N2 influenza virus surveillance throughout this region to aid pandemic prediction and prevention.